TRANSFER PRICING RISK ASSESSMENT: UN GUIDELINES, PRACTICES IN AUSTRALIA, AND RECOMMENDATIONS FOR INDONESIA - Meiliana, Meiliana; Tambunan, Maria R.U.D. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The Directorate General of Taxes has implemented the Compliance Risk Management (CRM) application, including the CRM Transfer Pricing (CRM TP) program, as a tool to map risks in transfer pricing practices. However, the effectiveness of CRM TP in ensuring compliance and preventing tax avoidance still requires further evaluation. According to a study by Maydiana (2023), the implementation of CRM faces various challenges, such as lack of support, data limitations, and insufficient system integration. At the international level, the United Nations (UN) guidelines for transfer pricing risk assessment have been successfully implemented in Australia. This research will explore the transfer pricing risk assessment approach by referring to the UN guidelines and Australia's experience, as well as provide strategic recommendations for The Directorate General of Taxes. The research employs a qualitative approach, using literature review as the method of data collection. The findings indicate that the assessment criteria, both quantitative and qualitative, do not accurately cover all relevant factors. Moreover, the effectiveness of the risk identification and monitoring processes also requires improvement, particularly in the use of data analysis applications that are not yet optimal and integrated. The monitoring and feedback mechanisms also need to be evaluated to be more adaptive to changing risks. The strategic recommendations proposed include the implementation of an integrated risk assessment approach, optimization of data utilization from Country by Country Reports, development of data analysis technology and monitoring systems, application of risk classification and compliance guidelines, as well as the enhancement of governance and documentation. These steps are expected to strengthen the transfer pricing risk assessment system, improve tax compliance, and create a more transparent business environment.